Dual channel sensor array based on ZnCdSe QDs – KMnO4: An effective tool for analysis of catechins and green teas. (October 2022) - Fan, Yao; Che, Siying; Zhang, Lei; Zhou, Chunsong; Fu, Haiyan; She, Yuanbin
Graphical abstract: Highlights: Dual channel sensor array based on ZnCdSe QDs - KMnO4 system was proposed. The sensor array took advantage of both "off" and "off–on" sensing modes. The "off–on" channel could detect various catechins. The sensor array could effectively distinguish green teas. Abstract: A novel dual-channel sensor array based on the "off" and "off–on" phenomenon of ZnCdSe quantum dots (QDs) - KMnO4 system was established for the effective distinguish of 30 green teas with various species, grades and origins. Starting from optimization of QDs for the construction of the sensing system, their sensitivity and selectivity performances towards 10 representative green teas were tested first and the sensor systems based on ZnCdSe QDs were finally established. An obvious "off" response brought by the interactions between amino acids, quercetin, et al. and ZnCdSe QDs was obtained while an "off–on" phenomenon brought by the interactions between catechins and the ZnCdSe-KMnO4 system had also been verified. Furthermore, based on the differential fluorescence "off–on" response of seven catechins, the qualitative and quantitative analyses of these catechins were successfully carried out with the linear range from 0.5 to 10 µg/mL. Most importantly, through adopting the dual-channel sensor, 30 green teas with different species, origins and grades can be accurately identified with the LDA model according to the spectral signals and the recognition accuracy could achieve 100 %.